Motivational Interviewing as an Adjunct to Cognitive Behavioral Therapy for Anxiety. Issue 1 (2nd December 2015) - Barrera, Terri L.; Smith, Angela H.; Norton, Peter J.
Abstract : Objective: This study examined the effect of a single session motivational interviewing (MI) intervention on engagement in a 12‐week transdiagnostic group cognitive behavioral therapy (CBT) treatment for anxiety. Method: Participants were randomized to MI ( N = 20) or non‐MI ( N = 19) conditions before enrolling in a 12‐week group CBT program. Participants in the MI condition received an individual 50‐minute MI session adapted from the longer MI pretreatment protocol, developed by Westra and Dozois (2003 ) and Westra (2012 ). Results: Rates of treatment initiation and treatment expectancies were significantly higher among participants who received the MI pretreatment intervention. Results indicate substantial reduction in clinician‐rated anxiety severity after transdiagnostic group CBT, with no significant differences between MI and non‐MI conditions. Conclusion: These findings suggest that a single MI pretreatment session may have positive effects on proximal measures of treatment engagement, but that these effects may not affect the severity of anxiety symptoms over the course of CBT.